2000
DOI: 10.1002/(sici)1097-4652(200002)182:2<150::aid-jcp3>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Role of HER2 gene overexpression in breast carcinoma

Abstract: The HER2 proto-oncogene encodes a transmembrane glycoprotein of 185 kDa (p185(HER2)) with intrinsic tyrosine kinase activity. Amplification of the HER2 gene and overexpression of its product induce cell transformation. Numerous studies have demonstrated the prognostic relevance of p185(HER2), which is overexpressed in 10% to 40% of human breast tumors. Recent data suggest that p185(HER2) is a ligand orphan receptor that amplifies the signal provided by other receptors of the HER family by heterodimerizing with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
149
0
9

Year Published

2001
2001
2013
2013

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 276 publications
(160 citation statements)
references
References 135 publications
(137 reference statements)
2
149
0
9
Order By: Relevance
“…Protein overexpression occurs in approximately 30% of breast cancers, particularly premenopausal breast cancer, and is associated with more aggressive disease and a poor prognosis in patients with positive lymph nodes. 41 Similar to investigations of antibody response to p53, endogenous humoral immunity to HER-2/neu directly correlates to overexpression of the protein by the patient's tumor, and HER-2/neu-specific autoantibodies can be detected in patients with early stage disease, indicating that the presence of antibodies are not simply a reflection of tumor burden. HER-2/neu antibodies at titers of >1:100 were detected in 12 of 107 (11%) breast cancer patients versus 0 of 200 (0%) controls (p < 0.01).…”
Section: Autoantibodies In Breast Cancermentioning
confidence: 83%
“…Protein overexpression occurs in approximately 30% of breast cancers, particularly premenopausal breast cancer, and is associated with more aggressive disease and a poor prognosis in patients with positive lymph nodes. 41 Similar to investigations of antibody response to p53, endogenous humoral immunity to HER-2/neu directly correlates to overexpression of the protein by the patient's tumor, and HER-2/neu-specific autoantibodies can be detected in patients with early stage disease, indicating that the presence of antibodies are not simply a reflection of tumor burden. HER-2/neu antibodies at titers of >1:100 were detected in 12 of 107 (11%) breast cancer patients versus 0 of 200 (0%) controls (p < 0.01).…”
Section: Autoantibodies In Breast Cancermentioning
confidence: 83%
“…Various clinical studies have evaluated the relationship between HER2 and breast cancer outcome, and most have shown that women with HER2-positive tumors have a poorer prognosis than women with HER2-negative tumors (Me´nard et al, 2000(Me´nard et al, , 2001bMasood and Bui, 2002). However, while the prognostic value of HER2 amplification/overexpression in node-positive patients has been widely demonstrated, there is no consensus on its value in node-negative cases (Press et al, 1997;Ross et al, 1998;Volpi et al, 2000;Cooke et al, 2001).…”
Section: Her2 Status In Prognosis and Prediction Of Response To Therapymentioning
confidence: 99%
“…[45][46][47] These two receptors stand at the origin of the major signaling pathway involved in the growth of breast cancer. EGFR amplification and activating mutations are rare events in breast cancer and differences in EGFR expression appear to be controlled largely at the transcriptional level.…”
Section: Impact Of Fhit On Her2-driven Breast Tumorsmentioning
confidence: 99%